Use of a covered self-expanding metal airway stent for severe dynamic collapse within a bronchial aortic graft conduit in a post-lung transplant patient. (2021) - Priebe, Rebecca; Duong, D. Kevin; Simoff, Michael J.; Mendoza, Javier Diaz; Debiane, Labib; Peralta, A. Rolando; Cohen, Avi
Abstract: We present a novel case in which a self-expanding, covered metal airway stent was utilized for severe dynamic collapse within a cadaveric aortic bronchial graft conduit in a post-lung transplant recipient with thoracic situs inversus.